2021
DOI: 10.3389/fgene.2021.650213
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Key Genes Involved in Aortic Valve Calcification Through Integrated Bioinformatics Analysis

Abstract: Background: Valvular heart disease is obtaining growing attention in the cardiovascular field and it is believed that calcific aortic valve disease (CAVD) is the most common valvular heart disease (VHD) in the world. CAVD does not have a fully effective treatment to delay its progression and the specific molecular mechanism of aortic valve calcification remains unclear.Materials and Methods: We obtained the gene expression datasets GSE12644 and GSE51472 from the public comprehensive free database GEO. Then, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 60 publications
4
7
0
Order By: Relevance
“…In addition, several chemokines, CCL18 [48] and CCL23 [49], have been associated with atherosclerosis. Similar to our results, several recent bioinformatic articles have reported that chemokine-related pathways and chemokines may play an important role in AVC [50,51]. In a study of the association between AVC and systemic lupus erythematosus (SLE) prognosis, Molad et al reported that AVC and mitral annular calcification (MAC) were significantly and positively associated with serum IgA isotype of anticardiolipin antibody [52].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, several chemokines, CCL18 [48] and CCL23 [49], have been associated with atherosclerosis. Similar to our results, several recent bioinformatic articles have reported that chemokine-related pathways and chemokines may play an important role in AVC [50,51]. In a study of the association between AVC and systemic lupus erythematosus (SLE) prognosis, Molad et al reported that AVC and mitral annular calcification (MAC) were significantly and positively associated with serum IgA isotype of anticardiolipin antibody [52].…”
Section: Discussionsupporting
confidence: 91%
“…Earlier studies on AVC patients reported that five genes ( CXCL16, GPM6A, BEX2, S100A9 , and SCARA5 ) are potential biomarkers of AVC, similar to the present findings ( 38 ). To date, however, comprehensive, strong, and reliable clinical decision-making approaches are lacking.…”
Section: Discussionsupporting
confidence: 92%
“…With the advancement of bioinformatics, efficient algorithms have accelerated the transition of various omics big data to new therapeutic targets. As one of the most robust algorithms for analyzing immune cell infiltration-CIBERSORT-has been used in multiple tissues [13][14][15][16]. In this study, we used it to explore the landscape of immune infiltration in the glomerulus of DN.…”
Section: Discussionmentioning
confidence: 99%